Fikih Prioritas dalam Fatwa Kehalalan Vaksin Covid-19 di Indonesia - Wahyu Akbar; Athoillah Islamy (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2022)
This study intends to identify the dimensions.of the priority fiqh paradigm(fiqh al-Awlawiyyât) in the formulation of the MUI Fatwa No. 02 of 2021 Regarding Covid-19 Vaccine Products From Sinovac Life Sciences Co. Ltd. China And Pt. Bio Farma (Persero). This qualitative research is in the form of a literature review using a philosophical normative approach. The analytical theory used is the priority fiqh paradigm that was initiated by Yusuf al-Qaradawi. The results showed that there were dimensions of the priority fiqh paradigm in the formulation of the MUI fatwa on the halalness of the Sinovac vaccine. First, the dimension of the fiqh al-maqasid paradigm (fiqh objectives) in the use of a theological foundation that contains a universal legal message about the importance of the orientation to maintain the benefit of the human soul (hifz nafs). Second, the dimension of the fiqh al-muwazanat paradigm (consideration fiqh) in the use of the basic principles of Islamic law (qawaid fiqhiyah) and classical fiqh thinking which emphasizes preventive efforts (saddal-dzari'ah) and universal benefit (maslahah mursalah). Meanwhile, the dimensions of the muwazanah fiqh paradigm can also be seen in the use of various classical fiqh opinions which are the basis for the formulation of the MUI fatwa, dominated by the opinions of the Shafi'i school of jurisprudence, which have acceptability for Muslims in Indonesia. Third, the dimension of the fiqh al-wâqi' paradigm (fiqh of reality) in the involvement of experts in the analysis of vaccines. This shows that MUI emphasizes the importance of integrating the formulation of fatwas with competent and developing scientific thinking, not just based on speculation. The theoretical implication of this research shows that the formulation of the MUI fatwa related to the halalness of the Sinovac vaccine has a paradigmatic priority scale for considering the level of benefit for life safety. The limitation of this research is that it has not examined the concrete role of MUI in disseminating the.fatwa on the halalness of the Sinovac vaccine as a form of synergy with the vaccination program in Indonesia